The intel microprocessors 8086/8088, 80186/80188, 80286, 80386, 80486, Pentium, Posesor Pentium Pro, Pentium II, Pentium III, dan Pentium 4 : Architecture, programming, and interfacing - Brey, Barry B. (Pearson Prentice Hall, 2006)
xi, 900 p. : il.; 26 cm